2012
DOI: 10.1108/17511061211238911
|View full text |Cite
|
Sign up to set email alerts
|

Environmental strategy: does it lead to competitive advantage in the US wine industry?

Abstract: Purpose -The purpose of this paper is to investigate and compare the perceptions of competitive advantage (cost leadership, differentiation, and performance) of those wineries which have implemented a clear business case for an environmental management system (EMS) and those which have not. Benefits and challenges of sustainability practices are also addressed. Design/methodology/approach -Data were collected via self-report web-based survey. Of the 98 respondents, over 80 per cent were family-owned, family-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 54 publications
6
72
1
4
Order By: Relevance
“…In the case of wineries, EP has a positive and significant effect on perceived corporate performance in line with the results obtained by Atkin et al [23]. The first hypothesis is therefore accepted despite the very low explained variance (11.6%).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the case of wineries, EP has a positive and significant effect on perceived corporate performance in line with the results obtained by Atkin et al [23]. The first hypothesis is therefore accepted despite the very low explained variance (11.6%).…”
Section: Discussionsupporting
confidence: 78%
“…These studies have focused on the factors leading to the adoption of an environmental management system (EMS) (e.g., [53,54]) or have examined subjects relating to consumer perceptions, brand image, or eco-labelling or eco-branding product differentiation strategies (e.g., [55,56]). Authors such as Atkin et al [23] go even further and attempt to confirm links between the adoption of an EMS and entrepreneurship in wineries, but are unable to link this adoption with any cost reduction. One reason given by the authors for this is that although costs can easily and quickly be quantified, benefits are often long term and harder to measure.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…In particular, businesses can reduce internal management costs as well as reducing and shortening the development and manufacturing process. Resource management in organizations is a cheap and effective technique to accomplish this [13][14][15][16][17].…”
Section: Competitive Advantagementioning
confidence: 99%
“…A consistent body of research can be found in the general management and business strategy literature, that analyses the role of people involved within the organization in promoting a sustainability orientation: various issues have been investigated such as the role of top management's values in determining sustainability orientation (Berry and Rondinelli 1998;Quazi 2003), entrepreneurial commitment to sustainability (Shaltegger 2002) or management practices and principles reshaped by a sustainability orientation (Atkin et al 2012;Warner 2007).…”
Section: Entrepreneurs and Top Managementmentioning
confidence: 99%